Is current smoking status and its relationship to anti-cyclic citrullinated peptide antibodies a predictor of worse response to biological therapies in rheumatoid arthritis patients?. (3rd September 2018) - Torrente-Segarra, V; Bergstra, SA; Solomon-Escoto, K; Da Silva, JAP; Veale, DJ; Al-Emadi, S; Huizinga, TWJ
Abstract : Objective : To assess the association between smoking, anti-cyclic citrullinated peptide (anti-CCP) antibody status, and clinical efficacy of biological therapies in rheumatoid arthritis (RA) patients. Method : This retrospective clinical practice setting study included 1349 RA patients from the METEOR database (aged >18 years). We collected data on sociodemographics, smoking status (smoker, <10, 10–19, and >20 cigarettes/day; ex-smoker; non-smoker), baseline disease activity parameters and anti-CCP, previous disease-modifying anti-rheumatic drugs (DMARDs), biological therapy, combined therapy (steroids and DMARDs), and follow-up disease activity. Clinical efficacy was assessed by European League Against Rheumatism (EULAR) good/moderate response rates for all aggregated biological therapies, based on both smoking and anti-CCP status. Results : The non-smoking RA patients were more often female at biological therapy initiation than the ex-smokers and smokers (91.1% vs 60.4% and 67.9%, respectively, p < 0.001), and ex-smokers were older than non-smokers and smokers (mean ± sd 56.5 ± 11.1, 53.5 ± 13.3 and 51.3 ± 11.0 years old, respectively; p < 0.001). In total, 845 (62.6%) were non-smokers, 214 (15.9%) ex-smokers, and 290 (21.5%) smokers [daily cigarettes smoked: 148 (11%) <11; 61 (4.5%) 11–20; and 81 (6%) >20]. Anti CCP-antibody status was similar in both groups. Non-smokers showed higher baseline DAS28 than ex-smokers and smokers (5.0 ± 1.5 vs 4.7 ± 1.4 and 4.7 ± 1.4, respectively; p < 0.001) and used more baseline steroids and DMARDs. A higher EULAR response rate was observed in non-smokers than in ex-smokers and smokers (73% vs 65% and 64.1%, respectively; p = 0.004). Drug survival was higher in non-smokers compared to ex-smokers and smokers [57.7 months (46.4–53.8), 38.6 (30.3–46.8), and 50.1 (41.8–58.4); p < 0.001, respectively]. Conclusion : In daily clinical practice, non-smokers respond better than smokers to biological therapy, but this does not result in better drug survival.